The role of insulin/IGF1 signalling in neurodevelopmental and neuropsychiatric disorders: evidence from human neuronal cell models - Réthelyi, János M.; Vincze, Katalin; Schall, Dorothea; Glennon, Jeffrey; Berkel, Simone (Neuroscience & biobehavioral reviews, 2023)
Insulin and insulin-like growth factor 1 (IGF1) signalling play a central role in the development and maintenance of neurons in the brain, and human neurodevelopmental as well as neuropsychiatric disorders have been linked to impaired insulin and IGF1 signalling. This review focuses on the impairments of the insulin and IGF1 signalling cascade in the context of neurodevelopmental and neuropsychiatric disorders, based on evidence from human neuronal cell models. Clear evidence was obtained for impaired insulin and IGF1 receptor downstream signalling in neurodevelopmental disorders, while the evidence for its role in neuropsychiatric disorders was less substantial. Human neuronal model systems can greatly add to our knowledge about insulin/IGF1 signalling in the brain, its role in restoring dendritic maturity, and complement results from clinical studies and animal models. Moreover, they represent a useful model for the development of new therapeutic strategies. Further research is needed to systematically investigate the exact role of the insulin/IGF1 signalling cascades in neurodevelopmental and neuropsychiatric disorders, and to elucidate the respective therapeutic implications.
Online veröffentlicht: 27. Juli 2023
Gesehen am 21.09.2023